From Conflict to Conviviality? Transforming Human–Bear Relations in Bulgaria - Toncheva, Svetoslava; Fletcher, Robert (Frontiers in Conservation Science, 2021)
The question of how to transform human-wildlife relations from conflict to coexistence, rather than merely mitigating conflicts, has become a central focus of research and practice. In this article, we address this important question by exploring the factors that may contribute to promoting successful coexistence between humans and brown bears within Europe and elsewhere. We do this through comparative analysis of two cases in rural Bulgaria evidencing different degrees of conflict and coexistence between members of the two species. Through this comparison, we highlight the main factors that lead to conflict in our problem case as well as those that might help to instead foster coexistence. We situate this analysis within growing discussion of convivial conservation (Büscher and Fletcher, 2020) as a novel approach intended to transform conservation policy and practice throughout the world that emphasizes the importance of attending to the overarching social and political-economic processes encompassing human-wildlife interaction in order to influence the latter. In this way, we contribute to research and discussion concerning how to transform human-wildlife conflict into convivial coexistence more broadly by demonstrating how attention to the immediate circumstances of human-wildlife encounter in such efforts should be complemented by promotion of more inclusive, democratic forms of decision-making and egalitarian distribution of economic resources.